2019
DOI: 10.3390/ijms20092319
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-B Receptor Directs Mitochondria-Associated Membranes to Regulate Vascular Smooth Muscle Cell Proliferation

Abstract: Mitochondria-associated membranes (MAM) are a well-recognized contact link between the mitochondria and endoplasmic reticulum that affects mitochondrial biology and vascular smooth muscle cells (VSMCs) proliferation via the regulation of mitochondrial Ca2+(Ca2+m) influx. Nogo-B receptor (NgBR) plays a vital role in proliferation, epithelial-mesenchymal transition, and chemoresistance of some tumors. Recent studies have revealed that downregulation of NgBR, which stimulates the proliferation of VSMCs, but the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Because Nogo-B is widely expressed in ER, it functions as a crucial protein for maintaining the ER-mitochondria unit (22) and plays an important role in protein folding, ER homeostasis, and lipid biosynthesis (23). It was recently reported Nogo-B can regulate the distance between ER and mitochondria when stress exists (24). Moreover, recent research demonstrated that upregulating Nogo-B expression helps to inhibit the proliferation of pulmonary artery smooth muscle cells, oxidative stress and ER stress (25).…”
Section: Discussionmentioning
confidence: 99%
“…Because Nogo-B is widely expressed in ER, it functions as a crucial protein for maintaining the ER-mitochondria unit (22) and plays an important role in protein folding, ER homeostasis, and lipid biosynthesis (23). It was recently reported Nogo-B can regulate the distance between ER and mitochondria when stress exists (24). Moreover, recent research demonstrated that upregulating Nogo-B expression helps to inhibit the proliferation of pulmonary artery smooth muscle cells, oxidative stress and ER stress (25).…”
Section: Discussionmentioning
confidence: 99%
“…Nogo-B receptor (NgBR) is a receptor that specifically binds to Nogo-B [18]. It is a single transmembrane protein that functions mainly in the remodeling and the formation of blood vessels [19][20][21]. Studies in recent years have shown that NgBR plays an essential role in tumor progression [22,23].…”
Section: Ivyspringmentioning
confidence: 99%
“…VSMC apoptosis accelerates atherogenesis and the progression of advanced lesions, leading to atherosclerotic plaque vulnerability and medial degeneration, suggesting MAM may be a new target to modulate VSMC fate and favor atherosclerotic plaque stability [23]. In addition, knocking out NgBR can cause MAM destruction and increase the phosphorylation of IPR3 through pAkt, is accompanied by mitochondrial dysfunction, including decreased Ca 2+ respiration and mitochondrial superoxide, and increased mitochondrial membrane potential and HIF-1α nuclear localization, indicating that the dysregulation of NgBR promotes VSMC proliferation through the destruction of MAM and the increase of IPR3 phosphorylation, thereby contributing to reduce Ca 2+ and mitochondrial damage [76].…”
Section: The Role Of Mam In the Development Of Atherosclerosismentioning
confidence: 99%